Bibliometric Mapping: Research Development on the Topic of Quality Management on Google Scholar Using Vosviewer - Kartikowati, Rr. Sri (Jurnal Ilmiah Peuradeun, 2024)
This research aims to map the development of quality management research indexed in Google Scholar and analyze topics related to this topic. By adopting a qualitative descriptive method, it was carried on through three stages: (1) indexed journal with the help of Google Scholar PoP (Publish or Perish) software; (2) journals were saved as an RIS (Research Information System) file; and (3) bibliometric analysis was performed using VOS viewer. This search focused on articles discussing quality management topics in the period 2010–2023, with a limit on the number of documents of 900. The research results showed that the amount of research on quality management had fluctuated. The most publications occurred in the specified year range, namely 83 articles. The topics most discussed were quality management systems, performance, top management, education, total quality management, relations, and improvement, while those that were still very few were distance education, skills, conflict management, competence, social development, information management, and career adaptability. Therefore, these topics were likely to be of concern to the latest research on quality management in the future because there was still very little research on them.